Assessment of skill performance in non-communicable disease services and job satisfaction among community health officers at Ayushman Arogya Mandirs in Raipur district: a cross-sectional study - Sahu, Dinesh Kumar; Sharma, Mini; Gupta, Shubhra A.; Jaisawal, Prashant; Agrawal, Shailendra; Sahu, Tarachand; Tripti (International Journal Of Community Medicine And Public Health, 2026)
Background: The Community Health Officers (CHOs) have a crucial position in the delivery of comprehensive primary health care services, especially for non-communicable diseases (NCDs). Their skill performance and job satisfaction are directly linked with the quality of service delivery and the success of the health system. This study aimed to assess the level of skill performance in selected NCD services like hypertension, diabetes mellitus, and oral cancer, and assess the job satisfaction among CHOs in Raipur district. Methods: The cross-sectional study was carried out from April to November 2024 in 70 CHOs from Ayushman Arogya Mandirs in Raipur district, selected by simple random sampling. A pretested semi-structured proforma based on the training module and McCloskey/Mueller Satisfaction Scale (MMSS) was used for collecting the data. Skill performance in NCD services like hypertension, diabetes mellitus, and oral cancer was measured by a binary scoring system in four domains: history taking, examination, diagnosis, and management. Results: The study found that the mean age of the participants was 28.86±3.4 years, with 85.7% being females. The Majority (60%) of study participants showed an average level of skill performance. Most participants (>95%) performed well in the diagnosis and management of hypertension and diabetes. In terms of job satisfaction, 68.6% reported a moderate level of job satisfaction among Community Health Officers. Conclusions: The study found that the majority of Community Health Officers performed at an average level of skill performance with a moderate level of job satisfaction. Induction training was found to have a significant effect on the performance of Community Health Officers.